Trends in environmental performance reporting in the Finnish forest industry - Marileena Mäkelä (Elsevier, 2022)
Previous content analyses of corporate reporting have typically focused on annual reports of one
reporting year of board samples. This paper focuses on one industry (the forest industry) and on its
environmental performance reporting over a 15-year period from 1998 to 2012. The aim of this research
is to analyse the reporting trends. The research is a case study of three Finnish forest industry companies’
reporting. Seven major trends emerged from the content analysis. For example, the companies report on
a massive number of indicators, focusing mainly on input and output indicators. Also, the number of
reported environmental performance indicators is decreasing in each indicator group. In addition, the
companies report on the environmental performance of their supply chain very little. This paper makes
two contributions. First, the decrease in the number of environmental performance indicators is highlighted;
the underlying reasons for the decrease should be researched further. Second, the paper pinpoints
the difficulty of obtaining a balanced view of environmental performance by looking at the
indicators alone, because these mainly focus on the inputs needed for production and on the unwanted
outputs caused (e.g. emissions and waste). This is an aspect that the report preparers should devote more
attention to in the future.